1985
DOI: 10.1111/j.1365-2125.1985.tb05110.x
|View full text |Cite
|
Sign up to set email alerts
|

Double‐blind trial of flurbiprofen and phenylbutazone in acute gouty arthritis.

Abstract: Flurbiprofen has been compared with phenylbutazone in a double-blind study involving 33 patients with acute gout. Patients received either flurbiprofen 400 mg daily for 48 h followed by 200 mg daily, or phenylbutazone 800 mg daily for 48 h followed by 400 mg daily. The drugs were of comparable efficacy, while side-effects were uncommon and relatively mild. Flurbiprofen appears to be a satisfactory alternative to phenylbutazone in the management of acute gouty arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 8 publications
(7 reference statements)
0
15
0
Order By: Relevance
“…Flurbiprofen (2-fluoro-α-methyl-4-biphenylacetic acid) is a representative 2-arylpropionic acid that can be used as a nonsteroidal anti-inflammatory drug (NSAID). Flurbiprofen (denoted hereafter as Fp) has been widely prescribed as an anti-inflammatory, antipyretic, and analgesic agent for several therapeutic applications such as pain from rheumatoid arthritis, sunburn , and acute gout, migraine headache, , osteoarthritis, soft tissue injuries (tendinitis and bursitis), , postoperative ocular inflammation (e.g., excimer laser photorefractive keratectomy), , vernal keratoconjunctivitis, ocular gingivitis, and herpetic stromal keratitis . Pharmacologically, Fp effects are mediated via inhibition of cyclooxygenase enzymes (COX-1 and COX-2, also referred to as prostaglandin H 2 synthases).…”
Section: Introductionmentioning
confidence: 99%
“…Flurbiprofen (2-fluoro-α-methyl-4-biphenylacetic acid) is a representative 2-arylpropionic acid that can be used as a nonsteroidal anti-inflammatory drug (NSAID). Flurbiprofen (denoted hereafter as Fp) has been widely prescribed as an anti-inflammatory, antipyretic, and analgesic agent for several therapeutic applications such as pain from rheumatoid arthritis, sunburn , and acute gout, migraine headache, , osteoarthritis, soft tissue injuries (tendinitis and bursitis), , postoperative ocular inflammation (e.g., excimer laser photorefractive keratectomy), , vernal keratoconjunctivitis, ocular gingivitis, and herpetic stromal keratitis . Pharmacologically, Fp effects are mediated via inhibition of cyclooxygenase enzymes (COX-1 and COX-2, also referred to as prostaglandin H 2 synthases).…”
Section: Introductionmentioning
confidence: 99%
“…21, The absolute risk for developing SAEs with AAD NSAID use was 2.3%. [32][33][34][35]37,39,41,[44][45][46][47]50,51,54 Interleukin (IL)-1 inhibitors are reported to be as effective as corticosteroids and NSAIDS for the treatment of acute gouty arthritis. 55 Unfortunately, these medicines are very expensive and are not widely available in many countries in the Asia-Pacific region.…”
Section: Among Patients With Acute Gouty Arthritis There Is Insufficient Evidence To Recommend For or Against The Use Of Intra-articular mentioning
confidence: 99%
“…Although only a few open-label studies have reported quantitative results, nearly all have concluded clinical benefit associated with short-term NSAID therapy. Controlled studies have employed comparator groups that have included indomethacin [34][35][36][37], phenylbutazone [38][39][40][41][42][43], or a different dose of the study drug [44,45]. Although generally deemed beneficial with good tolerability, there have been no substantial differences between the study agents and comparator drugs.…”
Section: Nonsteroidal Anti-inflammatory Drugsmentioning
confidence: 99%